Determination of Radiation Dose Rate in Radiology Installations Using Raysafe X2 Surveymeter - Andriati, Susi; Irka, Feriska Handayani; Firmawati, Nini; Wahyuni, Ade; Fardela, Ramacos (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
Based on the study of radiation dose rates in the Radiology Installation of Pariaman Regional Hospital using a Raysafe surveymeter, it can be reported that the radiation dose rate in the CT-Scan room is measured at (0.30-1.27) μSv/hour. In the conventional X-ray room, the radiation dose rate is found to be between (0.2-0.5) μSv/hour, while in the mammography room, the dose rate ranges from (0.00-0.40) μSv/hour. These findings indicate that the highest radiation exposure occurs in the CT-Scan room, which aligns with the higher complexity and intensity of the imaging procedures performed there. The relatively low dose rates in the conventional X-ray and mammography rooms suggest effective radiation shielding and adherence to safety protocols. Continuous monitoring of radiation levels is essential to ensure they remain within safe limits for both patients and medical staff. Furthermore, this data can be instrumental in optimizing exposure parameters, helping to minimize unnecessary radiation exposure while maintaining diagnostic quality. Implementing regular training for staff on radiation safety practices is also critical, as it enhances awareness and adherence to established protocols. Overall, these measures contribute to a safer radiology environment for all involved.